Legal origin and financial development: new evidence for old claims?the creditor rights index revisited - Michael Graff (ETH Zurich, KOF Swiss Economic Institute, 2008)
The law and finance theory predicts that the common law system provides the best basis for financial development and economic growth, followed by Scandinavian and German origin civil law and finally French origin civil law. This paper summarises the key points of the theory as well as a number of sceptical views. Moreover, it argues that the theory faces an identification problem, since the majority of common law countries have a market-based financial system, whereas the majority of civil law countries have a bank-based financial system. Furthermore, it is shown that one of the corner stones of the law and finance theory, its proposition that a common legal tradition implies a similar set of legal rules and procedure to protect financial investors, does not hold empirically. Last but not least, it is shown that recent additions to the theory's creditor right indicators data pool are eliminating the (weak) correspondence between business law and legal family that could be found in the original data set. Accordingly, the theory's claim that creditor protection is largely determined by the legal tradition of a particular country has to be reconsidered.
Keywords: K22; G20; P00; 330; Legal Tradition; Creditor Rights; Rechtsordnung; Wirtschaftswachstum; Gläubigerschutz; Finanztheorie; Rechtsökonomik; Europa